Evaluating Glacial Lakes Behavior in the High Himalayan Ranges of Pakistan: Glacial Lakes behavior in the High Himalayan ranges - Ashraf, Arshad; Naz, Rozina; Ahmad, Bashir; Raza, Irum (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
The increase in frequency of glacial lakes outburst floods resulting from changing climatic conditions in the recent years demands understanding of the existing situation of glacial lakes behavior in the Hindu Kush-Karakoram-Himalaya (HKH) ranges of Pakistan. The dynamics of glacial lakes was studied in relation with physical characteristics of the lakes and their surrounding using base data generated through integration of geographic information system and remote sensing data of 2001 and 2013 periods. The relationship analysis between lake area and elevation revealed that large sized lakes may decrease in numbers with altitude. The expansion of lakes and elevation had shown a positive correlation for all three HKH ranges, significant (P<0.05) for Karakoram range only. The correlation between lake expansion and aspect was non-significant for all three ranges. Future studies based on high resolution image data coupled with in-situ information are required to explore specific behavior of glacial lakes under various influential factors in the high altitude Himalayan ranges.